(untitled) (IAHS Medical Journal, 2024)
Background: A cataract is a cloudy area in the lens of the eye that leads to a decrease in vision. To describe the ocular demographic characteristics in relation to cataract blindness and cataract surgical coverage and to assess the visual outcome of cataract surgery is the objective of carrying out the study. Materials and methods: It was a retrospective study conducted during the period between February 2018 and February 2020 at Chattogram Lion’s Eye Institute and Hospital. 555 individuals age 20-119 years were selected using probability proportional to size sampling. Written informed consent was obtained from all eligible patients. All patients underwent basic eye examination by ophthalmologist. Visual impairment was determined for each eye according to standard WHO categorization. Results: The participation rate was 94.95%. This include 292 males and 263 females (M:F,1:1.3). The age range was 20 to 119 years with a range of 63.46± 11.91 years (63.67±12.65 years in male and 63.17 11.05 years in females). Most of the patients (n=213, 38.36%, 95% CI: 1.49-2.49%) were aged 60 years and above. 407 patients (M:F- 40.54%:32.79%) had cataract in both eyes, 148 (M:F-14.41%:12.25%) had in one eye. Among them previous cataract surgery 34 (M:F=3.60%: 2.52%) had uniocular pseudophakia. However, cataract surgical coverage rates were lower for female than male. 58.43% eyes with cataract surgery had good VA (6/6 - 6/18). Conclusion: The study highlights high prevalence of blinding cataract as compared to Chattogram region. Education and early disease awareness and access to cataract surgical services would play an important role to increase the CSR in the area and presupposes the extended role of Chattogram Lions Eye Institute and Hospital and similar eye care providers in the area. IAHS Medical Journal Vol 6(1), June 2023; 6-9